Różnorodne formy apokalipsy w literaturze popularnej - Bartos, Rafał (Annales Missiologici Posnanienses, 2021)
The main objective of the paper is to discuss the theme of apocalypse and post-apocalypse used by popular literature creators. Four types of possible apocalypses will be analyzed and will be examinated, each with an example from literature. The sources of contemporary apocalypse and the consequences of introducing the theme into fantastic worlds will also be described. This theme is popular with creators and is also of great interest to the public, especially nowadays.